Short-Term High- and Moderate-Intensity Training Modifies Inflammatory and Metabolic Factors in Response to Acute Exercise - Lira, Fabio Santos; dos Santos, Thaislaine; Caldeira, Renan Santos; Inoue, Daniela S.; Panissa, Valéria L. G.; Cabral-Santos, Carolina; Campos, Eduardo Z.; Rodrigues, Bruno; Monteiro, Paula A. (Frontiers in Physiology, 2017)
PURPOSE: To compare the acute and chronic effects of high intensity intermittent training (HIIT) and steady state training (SST) on the metabolic profile and inflammatory response in physically active men. METHODS: Thirty recreationally active men were randomly allocated to a control group (n = 10), HIIT group (n = 10), or SST group (n = 10). For five weeks, three times per week, subjects performed HIIT (5km 1-min at 100% of maximal aerobic speed interspersed by 1-min passive recovery) or SST (5km at 70% of maximal aerobic speed) while the control group did not perform training. Blood samples were collected at fasting (~12h), pre-exercise, immediately post, and 60 minutes post-acute exercise session (pre and post 5 weeks training). Blood samples were analyzed for glucose, non-ester fatty acid (NEFA), and cytokine (IL-6, IL-10, and TNF-α) levels through a three-way analysis (group, period, and time of measurement) with repeated measures in the second and third factors. RESULTS: The results showed an effect of moment of measurement (acute session) with greater values to TNF-α and glucose immediately post the exercise when compared to pre exercise session, independently of group or training period. For IL-6 there was an interaction effect for group and moment of measurement (acute session) the increase occurred immediately post exercise session and post-60 min in the HIIT group while in the SST the increase was observed only 60 minutes post, independently of training period. For IL-10, there was an interaction for training period (pre and post training) and moment of measurement (acute session), in which in pre-training, pre-exercise values were lower than immediately and 60 min post-exercise in post-training period pre-exercise values were lower than immediately post-exercise and immediately post-exercise lower than 60min post, it was also observed that values immediately post-exercise were lower pre- than post-training , being all results independently of intensity (group). CONCLUSION: Our main result point to an interaction (acute and chronic) for IL-10 showing attenuation post training period independent of exercise intensity.